2010
DOI: 10.1111/j.1748-1716.2010.02129.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of muscle blood flow during exercise: local factors and integrative mechanisms

Abstract: Understanding the control mechanisms of blood flow within the vasculature of skeletal muscle is clearly fascinating from a theoretical point of view due to the extremely tight coupling of tissue oxygen demands and blood flow. It also has practical implications as impairment of muscle blood flow and its prevention/reversal by exercise training has a major impact on widespread diseases such as hypertension and diabetes. Here we analyse the role of mediators generated by skeletal muscle activity on smooth muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(145 citation statements)
references
References 154 publications
(187 reference statements)
4
138
3
Order By: Relevance
“…Late vasodilatation is mostly mediated by accumulation of local vasoactive compounds, which act directly on the vessel wall and indirectly to block sympathetic activation (functional sympatholysis). Indeed several investigators have confirmed that sympathetic vasomotor innervation is activated during exercise (52,(54)(55)(56). Despite the similar local vasodilatation occurring in both groups, relative flow at high exercise load was significantly higher in trained SHR than in trained WKY ( Figure 5), suggesting the involvement of other factor(s).…”
Section: Effects Of Training On Blood Flowmentioning
confidence: 72%
“…Late vasodilatation is mostly mediated by accumulation of local vasoactive compounds, which act directly on the vessel wall and indirectly to block sympathetic activation (functional sympatholysis). Indeed several investigators have confirmed that sympathetic vasomotor innervation is activated during exercise (52,(54)(55)(56). Despite the similar local vasodilatation occurring in both groups, relative flow at high exercise load was significantly higher in trained SHR than in trained WKY ( Figure 5), suggesting the involvement of other factor(s).…”
Section: Effects Of Training On Blood Flowmentioning
confidence: 72%
“…As the depolarization spreads into distant VSMCs, L-type channels are activated and the concomitant Ca 2 þ entry and rise in [Ca 2 þ ] i leads to conducted vasoconstriction. In the latter case where a transient local vasoconstriction is followed by a secondary conducted vasodilatation, evidence has shown that a local G a/qmediated IP 3 [48][49][50][51] Application of a local high KCl concentration has also been widely used as a tool to induce conducted depolarization and vasoconstriction. This leads to a conducted vasoconstriction of rather limited amplitude, which is thought to rely primarily on intercellular communication via the VSMC layer.…”
Section: How Vascular Conducted Responses Are Typically Measuredmentioning
confidence: 99%
“…1 Theoretical work, however, suggests that in arteriolar networks nonlocal mechanisms are necessary for achieving optimal performance with regard to the delivery of oxygen and nutrients. 2,3 It has been speculated that vascular conducted responses (VCRs) could be such a nonlocal mechanism and thereby assist in coordinating and enhancing the effects of changes in local vascular resistances in brain arteriolar networks and thereby contribute to the effective and highly dynamic distribution of blood flow to areas of the brain undergoing large changes in neuronal activity. 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…The observed increase in the elasticity of blood vessels in the present study indicated by an increase in the amplitude of the wave pulse and systolic slope of the pulse wave may be due to the previously mentioned increase in the reactivity of the endothelium in the form of an increased propensity for mediated vasodilatation dependent on the flow. The explanation for this phenomenon lies mainly in increases in endothelial nitric oxide production [25].…”
Section: Discussionmentioning
confidence: 99%